Studi Dasar Mengenai Beton yang Menggunakan Agregat Buatan yang Ringan Sebagai Agregat Kasar - Tjaronge, Muhammad Wihardi (MEDIA KOMUNIKASI TEKNIK SIPIL, 2005)
Recently, concrete containing artificial light weight aggregates  were used to produce the light weight element of structures.　Most of the previous research has been carried out on the concrete containing artificial light weight aggregates as coarse aggregate and fine aggregate.  This research is a fundemental study on the concrete containing artificial lightweight aggregates as coarse aggregate and river sand as fine aggregate. The artificial lightweight aggregates  is made from expanded shale. Experimental tests consisted of measuring the slump, air content of the fresh concrete and compressive strength of hardened concrete. Test result revealed that the concrete containing artificial lightweight aggregates as coarse aggregate and river sand as fine aggregate can attain the  slump design,   air content design,  compressive strength design and flexural strength.Keywords : agregat kasar buatan yang ringan, beton ringan, slump, kandungan udara, kuat tekan dan kuat lenturPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3900[How to cite: Tjaronge, M.W., 2005, Studi Dasar Mengenai Beton yang Menggunakan Agregat Buatan yang Ringan Sebagai Agregat Kasar, Jurnal Media Komunikasi Teknik Sipil, Volume 13, Nomor 1, pp. 88-95]